2018
DOI: 10.3389/fpls.2018.01912
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies to Improve Wood Properties: Challenges and Prospects

Abstract: Wood formation is an excellent model system for quantitative trait analysis due to the strong associations between the transcriptional and metabolic traits that contribute to this complex process. Investigating the genetic architecture and regulatory mechanisms underlying wood formation will enhance our understanding of the quantitative genetics and genomics of complex phenotypic variation. Genome-wide association studies (GWASs) represent an ideal statistical strategy for dissecting the genetic basis of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 90 publications
0
29
0
Order By: Relevance
“…The QTL detected in our study explain a small proportion of the genetic variation and this could be due to several factors. This is in line with previous studies examining genetic variation in complex traits in coniferous species using forward genetic approaches, such as QTL (Sewell et al ., ; Novaes et al ., ) and AM (Wegrzyn et al ., ; Du et al ., , ; Porth et al ., ; McKown et al ., ; Lamara et al ., ) The large effective population size in forest tree populations closely resembles humans, therefore making the ‘missing heritability’ issue found in human AM experiments relevant to forest tree populations. First, one of the hypothesis attributed to this ‘missing heritability’ is the substantial amount of quantitative variation linked to the cumulative effect of rare alleles that cannot be detected in GWAS using small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The QTL detected in our study explain a small proportion of the genetic variation and this could be due to several factors. This is in line with previous studies examining genetic variation in complex traits in coniferous species using forward genetic approaches, such as QTL (Sewell et al ., ; Novaes et al ., ) and AM (Wegrzyn et al ., ; Du et al ., , ; Porth et al ., ; McKown et al ., ; Lamara et al ., ) The large effective population size in forest tree populations closely resembles humans, therefore making the ‘missing heritability’ issue found in human AM experiments relevant to forest tree populations. First, one of the hypothesis attributed to this ‘missing heritability’ is the substantial amount of quantitative variation linked to the cumulative effect of rare alleles that cannot be detected in GWAS using small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…GWAS is a powerful tool to detect marker-traits associations using genotypic collections inclusive of long recombination histories, which promises to achieve deep mapping resolutions, and save the time needed to set up experimental populations for QTL mapping (Bernardo, 2016). Because of their high genetic diversity, undomesticated status, and generally fast linkage disequilibrium (LD) decay, lignocellulosic crops -especially biomass trees -appear ideal for GWAS (Du et al, 2018), and several studies have thus used this approach to reveal loci underlying biomass-related traits. For example, GWAS has been used in poplar to detect several marker-trait associations for quality characters as lignin content and composition (Porth et al, 2013), as well as for phenology traits as canopy duration or flowering date (McKown et al, 2014).…”
Section: Tools and Strategies To Advance Promising Lignocellulosic Pementioning
confidence: 99%
“…Despite GWAS promises, Fahrenkrog et al (2017) have pointed out how rare allele variants, whose detection can be quite often missed by GWAS analyses (Bernardo, 2016), can be particularly relevant to explain genetic variation for bioenergy traits as cell wall composition. Therefore, good experimental designs (e.g., adequate sample size and geographical sampling of accessions to give a balanced representation of the variability for a trait of interest in the panel used; Brachi et al, 2011) are pivotal to successfully perform a GWAS (Du et al, 2018). As for QTL mapping, GWAS results can be directly used for MAS (Allwright and Taylor, 2016).…”
Section: Tools and Strategies To Advance Promising Lignocellulosic Pementioning
confidence: 99%
“…Several large-scale genome-wide association studies have identified the underlying genetic architecture related to morphological, physiological, wood property and chemistry, salinity tolerance, and disease resistance traits ( Ma et al, 2013 ; McKown et al, 2014b ; Muchero et al, 2015 ; Zhang et al, 2018 ; Bdeir et al, 2019 ; Quan et al, 2019 ; Jia et al, 2020 ; Lu et al, 2020 ). Furthermore, the biology of wood formation, cell wall ultrastructure and composition, and cell wall recalcitrance are fairly well studied ( Groover et al, 2010 ; Wegrzyn et al, 2010 ; Studer et al, 2011 ; Du et al, 2013 ; Porth et al, 2013a ; Porth et al, 2013b ; Muchero et al, 2015 ; Porth et al, 2015 ; Allwright et al, 2016 ; Du et al, 2016 ; Escamez et al, 2017 ; Fahrenkrog et al, 2017 ; Johnson et al, 2017 ; Xi et al, 2017 ; Du et al, 2018 ; Gandla et al, 2018 ; Du et al, 2019 ) and a few studies have also recognized the role of microRNA in controlling tree growth and wood property traits in Populus ( Quan et al, 2016 ; Chen B. et al, 2018 ). However, the genetic architecture underlying wood anatomical traits such as vessel size and density are relatively uncharacterized, despite the importance of these traits for cell wall composition and the overall performance of the tree.…”
Section: Introductionmentioning
confidence: 99%